Pengaruh Profitabilitas, Likuiditas dan Solvabilitas Terhadap Harga Saham pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2024 - Abdul Aziz; Dian Anita Sari (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to examine how profitability, liquidity, and solvency influence stock price movements in banking companies listed on the Indonesia Stock Exchange during 2020-2024. A quantitative approach was employed in this study, with the population encompassing all banking companies listed on the IDX during the observation period. The study sample was determined using purposive sampling, resulting in the selection of 45 banking companies. The data analyzed is secondary, obtained from annual reports of banking companies released on their official websites and the NAIK application. The data analysis stage includes descriptive statistics and multiple linear regression analysis. Before testing the hypotheses, classical assumption tests were run on the data to ensure the validity of the study model. Hypothesis testing was conducted using a partial t-test, while the model's ability to explain stock price variations was assessed using the coefficient of determination (R²). This study demonstrates that profitability has a positive and significant impact on stock prices, while liquidity and solvency have a negative but insignificant impact on stock prices.